Women Anthropologists and Detective Writing - Salamone, Frank A. (IJRDO - Journal of Social Science and Humanities Research, 2016)
The purpose of anthropology is to make the world safe for human differences. Ruth Benedict The Eternal Feminine and the Eternal Male in Western Thought There has long been an overt or covert belief in the innate difference between males and females in Euro-American culture. Even those who may deny the innateness of the dichotomy and of its biological roots will hold for its cultural truthfulness. At least this modified position holds out for possible change and that things can be other than they are. However, the consequences of the dichotomy, whatever its root source in nature or culture (nature/nurture) is the same: woman is put on a pedestal and man is demonized. This view has consequences for female novelists which can limit their subject matter and their treatment of it.